1980
DOI: 10.1172/jci109936
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic manifestations of human anaphylaxis.

Abstract: A B S T R A C T In the course of a controlled study to evaluate different forms of immunotherapy for subjects with insect-sting hypersensitivity, we observed 11 subjects who had systemic cutaneous urticarial reactions and 3 subjects who experienced systemic anaphylaxis. With the exception of tachyeardia, there were no cardiopulmonary changes in the subjects with urticaria, whereas the major manifestation of anaphylactic shock in the other three subjects was severe hypotension that was probably secondary to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0
14

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(160 citation statements)
references
References 26 publications
4
142
0
14
Order By: Relevance
“…In their study based on 2 databases covering a population with employer-sponsored health insurance and individuals aged ≥65 years, Clark et al [6] found that patients with more severe anaphylaxis (leading to admission) had a higher Charlson-Deyo score (modified Charlson comorbidity index) [30,31], a higher number of laboratory/radiology tests performed during the year before admission, or a visit to the emergency department or admission (any cause) during the previous year. Both these findings and ours suggest that more severe anaphylaxis episodes were associated with more severe previous comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In their study based on 2 databases covering a population with employer-sponsored health insurance and individuals aged ≥65 years, Clark et al [6] found that patients with more severe anaphylaxis (leading to admission) had a higher Charlson-Deyo score (modified Charlson comorbidity index) [30,31], a higher number of laboratory/radiology tests performed during the year before admission, or a visit to the emergency department or admission (any cause) during the previous year. Both these findings and ours suggest that more severe anaphylaxis episodes were associated with more severe previous comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…ere is increasing evidence of cardiac involvement in human anaphylaxis too [8,9,12,13]. Initially this has been attributed to mediators originating from the lung and reaching the heart.…”
Section: Hhmc In Systemic and Cardiac Anaphylaxismentioning
confidence: 99%
“…HHMC possess FcεRI, C3a receptor (C3aR), and C5a receptor (C5aR) bound to their membrane surface. erefore, it is likely that IgE-, C5a-, and C3a-mediated activation of these cells could play a role in systemic and cardiac anaphylaxis in humans [9,12,13].…”
Section: Hhmc In Systemic and Cardiac Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the plasma KKS can be considered to have a spectrum of physiological effects, ranging at one extreme from a hemostatic state of vasodilation and promotion of smooth blood flow, all the way to a prothrombotic state. It is conceivable to suggest that other mechanisms proposed about respiratory, retinal, and renal systems can fit into this spectrum of physiological effects (1)(2)(3). There is accumulating evidence suggesting that when the plasma KKS is activated, the results are a sequential release of proteolytic enzymes and vasoactive peptides, generation of both angiogenic and anti-angiogenic molecules, stabilization of thrombus, and an increase in protease inhibitor activity in blood (4 -7).…”
mentioning
confidence: 99%